As emoções percebidas através das paisagens sonoras: a compreensão do estresse laboral em professoras da educação básica de São Luís – MA - DINIZ NETO, Alberto Joaquim Goveia (2024)
The teaching work of teachers in the basic education network can be understood based on forms of illness, in which work stress is one of these and relevant. This psychological construct exerts influence in different areas for human beings, both in emotional, as well as social and cultural aspects. Symptoms of work stress are similar to dysfunctions in basic emotions, an aspect that points to the proximity of this illness to this sphere of human subjectivity. Basic emotions are classified as the basis of emotional functioning, subdivided into six major areas, which are: happiness, sadness, anger, fear, surprise and disgust. From these emotions, others are developed throughout human development and, when activated, help individuals in situations from different perspectives. In the school setting, emotions appear in different ways, as they depend on the relationships that are established in that location and the different landscapes that construct this space, whether visual or sound. In this research, we sought to relate basic emotions with the school's soundscapes in order to understand the correlation with work stress in teachers who work in Basic Education. 31 practicing teachers participated in the research, the research instruments were the Characterization Questionnaire, which sought to identify social and educational data, the Perceived Stress Scale which sought to evaluate stress indices, the Sound Drawing which sought, based on colorful drawings, identify emotions and the sounds of emotions for the participants. The results showed the relationship between perceived stress and high working hours, while the main highlighted emotions present in schools were anger, sadness, fear and disgust. With this, it is concluded that the school space can also be configured as a promoter of illness, and that different actions need to occur to develop the health and well-being of teachers.